Te Kete Tuawhā, Te Kete Aronui - The Fourth Basket - Kāretu, Tīmoti (Te Kaharoa, 2008)
This article extends on the notion of the traditional Maori notion of three baskets of knowledge by adding a fourth category. The author draws on an extensive quantity of literature, over a diverse range of disciplines, with a general focus on the role of Te Reo Maori (the Maori language) in the modern world.